Sultan Hamengku Buwono IX: Manuver Stabilisasi dan Rehabilitasi Perekonomian Indonesia Awal Orde Baru - Rizal Zamzami (Institut Agama Islam Negeri Jember, 2021)
Abstract The purpose of this paper is to describe the strategic steps for completing the stabilization and rehabilitation of the early New Order economy. The method used is a qualitative method using a historical approach and economic theory to examine the economic maneuvers of Sultan HB IX. The research method used is a historical research method in which there are 5 stages: topic selection, heuristics, source criticism, interpretation, and historiography. The result of this research is that after Sultan HB IX occupied strategic positions, namely Waperdam Ekubang, Menutama EKKU, and Minister of EKUIN in the government. Sultan HB IX issued his political-economic statement which also became a maneuver to solve problems in the economic field. From the results of these studies, it can be concluded that the solution to economic problems at the beginning of the new order was by taking actions at home and abroad which would provide a positive stimulus for the Indonesian economy.